A 3D-printed transepidermal microprojection array for human skin microbiome sampling - Liang, Kun (2023)
Skin microbiome sampling is currently performed with tools such as swabs and tape strips to collect microbes from the skin surface. However, these conventional approaches may be unable to detect microbes deeper in the epidermis or in epidermal invaginations. We describe a sampling tool with a depth component, a transepidermal microprojection array (MPA), which captures microbial biomass from both the epidermal surface and deeper skin layers. We leveraged the rapid customizability of 3D printing to enable systematic optimization of MPA for human skin sampling. Evaluation of sampling efficacy on human scalp revealed the optimized MPA was comparable in sensitivity to swab and superior to tape strip, especially for nonstandard skin surfaces. We observed differences in species diversity, with the MPA detecting clinically relevant fungi more often than other approaches. This work delivers a tool in the complex field of skin microbiome sampling to potentially address gaps in our understanding of its role in health and disease.